ASASSN-18am/SN 2018gk: an overluminous Type IIb supernova from a massive progenitor. Issue 3 (4th March 2021) - Bose, Subhash; Dong, Subo; Kochanek, C S; Stritzinger, M D; Ashall, Chris; Benetti, Stefano; Falco, E; Filippenko, Alexei V; Pastorello, Andrea; Prieto, Jose L; Somero, Auni; Sukhbold, Tuguldur; et al.
ABSTRACT: ASASSN-18am/SN 2018gk is a newly discovered member of the rare group of luminous, hydrogen-rich supernovae (SNe) with a peak absolute magnitude of MV ≈ −20 mag that is in between normal core-collapse SNe and superluminous SNe. These SNe show no prominent spectroscopic signatures of ejecta interacting with circumstellar material (CSM), and their powering mechanism is debated. ASASSN-18am declines extremely rapidly for a Type II SN, with a photospheric-phase decline rate of ∼6.0 mag (100 d) −1 . Owing to the weakening of H i and the appearance of He i in its later phases, ASASSN-18am is spectroscopically a Type IIb SN with a partially stripped envelope. However, its photometric and spectroscopic evolution shows significant differences from typical SNe IIb. Using a radiative diffusion model, we find that the light curve requires a high synthesized 56 Ni mass M_Ni 0.4 M_ and ejecta with high kinetic energy E kin = (7–10) × 10 51 erg. Introducing a magnetar central engine still requires M_Ni 0.3 M_ and E kin = 3 × 10 51 erg. The high 56 Ni mass is consistent with strong iron-group nebular lines in its spectra, which are also similar to several SNe Ic-BL with high 56 Ni yields. The earliest spectrum shows 'flash ionization' features, from which we estimate a mass-loss rate of M≈ 2× 10^-4 M_ yr^-1 . This wind density is too low to power the luminous light curve by ejecta–CSM interaction. We measure expansion velocities as high as 17 000 km s^-1 for Hα, which is remarkably high compared to other SNe II. We estimate an oxygen core mass of 1.8–3.4 M⊙ using the [O i ] luminosity measured from a nebular-phase spectrum, implying a progenitor with a zero-age main-sequence mass of 19–26 M⊙ .